Deep brain stimulation for neuropathic pain. - Owen, S; Green, A; Nandi, D; Bittar, R; Wang, S; Aziz, T (2007)
Deep brain stimulation (DBS) for pain was one of the earliest indications for the therapy. This study reports the outcome of DBS of the sensory thalamus and the periventricular and peri-aqueductal grey area (PVG/PAG) complex for different intractable neuropathic pain syndromes. Forty-seven patients (30 males and 17 females) were selected for surgery; they were suffering from any of the following types of pain: post-stroke neuropathic pain, phantom limb pain, post-herpetic neuralgia, anaesthesia dolorosa, brachial plexus injury and neuropathic pain secondary to neural damage from a variety of causes. Of the 47 patients selected for trial stimulation, 38 patients proceeded to permanent implantation. Patients suffering from post-stroke pain were the most likely to fail trial stimulation (33%), in contrast to individuals with phantom limb/post-brachial plexus injury pain and anaesthesia dolorosa, all of whom underwent permanent implantation. PVG stimulation alone was optimal in 17 patients (53%), whilst a combination of PVG and thalamic stimulation produced the greatest degree of analgesia in 11 patients (34%). Thalamic stimulation alone was optimal in 4 patients (13%). DBS of the PVG alone was associated with the highest degree of pain alleviation, with a mean improvement of 59% (p <0.001) and a > or =50% improvement in 66% of patients. Post-stroke pain responds in 70% of patients. We conclude that the outcomes of surgery appear to vary according to aetiology, but it would appear that the effects are best for phantom limb syndromes, head pain and anaesthesia dolorosa.